The Landry News - Clements, Andrew (Simon & Schuster Simon & Schuster, 1999)
A fifth-grader starts a newspaper with an editorial that prompts her burnt-out classroom teacher to really begin teaching again, but he is later threatened with disciplinary aaction as a result.
5.7
5-9
Bluebonnet
Keywords: Schools; newspapers; fiction; Teachers; Fiction; Fiction